Analisis Kerusakan Serta Masalah Prosesor Komputer Menggunakan Sistem Pakar - Kevin Ronald Sragarta; Riga Saputra Dewa; Rahima Mahabbah; Ilham Firdaus; Didik Aribowo (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
Knowledge about damage that often occurs to computer processors and how to handle this damage with experts is very important. The method used in this research is a literature study with descriptive explanations, where the author looks for as many references as possible regarding problems that often occur, especially computer processor damage and how to overcome them. The research results show that the dual-core capabilities of the processor can be utilized as optimally as possible by managing the use of processor resources by server applications that run simultaneously on the server computer, and also ensuring that the applications being run can work well. Damage that often occurs in computer software is generally related to problems with the operating system, applications or files used. Therefore, an expert system is a computer system designed to imitate human abilities in diagnosing problems or providing solutions based on their knowledge and experience in the context of computer processor failure..